Pemodelan Enterprise Arsitektur Sistem Informasi Pemesanan Jasa Percetakan Menggunakan Kerangka TOGAF - Sudarsono, Bibit -; Faddillah, Umi - (REMIK: Riset dan E-Jurnal Manajemen Informatika Komputer, 2020)
Printing service order information systems sometimes experience problems in completing running business processes including, frequent loss and inaccuracy in registering orders from customers, often also losing order data from customers, recording orders often experience errors, resulting inaccurate reporting of order data. A computerized ordering service information system will greatly help improve performance and accuracy in making reports on business processes running at a company. The existence of enterprise modeling of information systems ordering printing services with the TOGAF framework will be a method that greatly helps management make a decision that will synergize with the business process activities at the company. So that the objectives of the system can be achieved properly. The TOGAF framework can be a solution and will help to produce a system architecture design, a business process architecture, a technology architecture, a number of proposed business opportunity strategy proposals and an ongoing system change proposal.